The Role of Government in Empowering Society Health in the Field of Maternal and Children Health in West Java - Sugyati, Cucu; Mariana, Dede; Suwaryo, Utang; Setiabudi Sumadinata, Widya (International Journal of Engineering and Technology, 2018)
This study conducts a profoundly systematic analysis of the role of government in establishing the society in the health sector, especially mother and child field in West Java, Indonesia. This descriptive-qualitative study presents a discussion of how the elements of public health implementers interact with societies in West Java Province, so their knowledge and experience increases their autonomy. This study employs the theory of health services and promotion. It finds that (a) services and networks of cooperation in public health institutions, within the provincial government of Java is quite uniform and well implemented; (B) the government plays an essential role in empowering people in the health sector. Nevertheless, there is a deficiency of health workers. That is, they are who directly maintain the health of mother and children as well as health promotion staff. Hence, this study highly recommends the incentives for volunteers of health task force coming from ordinary people.Â Â